A Pilot Study: The Effect of Sunnah Bedtime Routines on the Memorizing and Problem-Solving Skills of University Students (ELEKTRIKA- Journal of Electrical Engineering, 2022)
Quality sleep is essential to maintain normal levels of cognitive skills. During sleep, electroencephalogram (EEG) is used to study brain activity to detect disorders. However, the effect of Sunnah bedtime routines on the brain cognitive performance is rarely studied. Therefore, this study was conducted to compare the effect of Sunnah bedtime routines on cognitive performance of ten male college students using cortical information pathway. The students were divided into Group 1 (control) and Group 2 (Sunnah bedtime routine). Members of Group 2 performed Sunnah bedtime routines for six weeks whereas members of Group 1 were not assigned to any particular routine. The participants’ memorizing and problem- solving abilities were assessed in the first and final week of the experiment. The subjects’ brain signals were recorded using EEG and Partial Directed Coherence (PDC) was applied to extract the cortical information pathway. The cortical connectivity and test scores between the two groups were compared. Members of Group 2 were shown to perform better than Group 1 in both abilities and EEG analysis show that the two groups were utilizing different parts of the brain region. In conclusion, this study highlighted the probable impact of Sunnah bedtime routines on the two cognitive skills.